Synthesis and structure of the gibbsite intercalation compounds [LiAl2(OH)(6)]X {X=Cl, Br, NO3} and [LiAl2(OH)(6)]Cl center dot H2O using synchrotron X-ray and neutron powder diffraction - Besserguenev, A; Fogg, A; Francis, R; Price, S; OHare, D; Isupov, V; Tolochko, B (1997)
Treatment of gibbsite {γ-Al(OH)3} with the lithium salts LiX {X = Cl, Br, NO3} in water leads to intercalation of both the cations and anions into the host structure to give [LiAl2-(OH)6]X·H2O {X = Cl, Br, NO3}. Thermogravimetric analysis indicates that these materials can be readily dehydrated to give highly hydroscopic, crystalline layered phases [LiAl2(OH)6]X {X = Cl, Br, NO3}. The structures of these dehydrated phases have been determined by synchrotron X-ray and neutron powder diffraction. The dehydrated intercalates with {X = Cl, Br} are isomorphous and crystallize in the P63/mcm space group. [LiAl2(OH)6]NO3 adopts a similar structure but crystallizes in space group P63/m due to disorder of the intercalated nitrate anions in the crystallographic ab plane. All the intercalates consist of eclipsed Al-(OH)3 layers stacked along the c-axis with the halide or nitrate ions located at the cell edges and midway between the Al(OH)3 layers. The lithium ions have been located in the unfilled octahedral sites within the Al(OH)3 layers. The structure of the hydrated phase [LiAl2-(OH)6]Cl·H2O has also been determined, it adopts a similar structure with eclipsed [LiAl2-(OH)6]+ layers stacking along the c-axis. However the intercalated Cl- ions and water molecules were found to be disordered over five sites located midway between the Al(OH)3 layers.